Meningkatkan Self Disclosure Siswa Menengah Kejuruan Menuju Era Society 5.0 dengan Art Psychotherapy - Anggraini, Helda Yusfarina; Sari, Nina Permata; Rachman, Ali (citeus, 2025)
Self Disclosure is essential for every individual to freely express himself and improve his emotional, cognitive, physical, and spiritual well-being. Art Psychotherapy can be used to increase Self Disclosure. This study aimed to determine the effectiveness of Art Psychotherapy in increasing Vocational high school students' Self Disclosure. A quasi-experimental design is used in this quantitative study. A total of six students of the eleventh grade Music Skills Program at SMK Negeri 4 Banjarmasin became the research sample selected using the purposive sampling technique. Art Psychotherapy is a treatment that is used and given in four meetings. The measuring instrument uses a scale of self-disclosure that has been tested for validity and reliability. Data analysis technique using Mann Whitney U Test and Wilcoxon Test. The result shows differences in the level of Self Disclosure before and after being given treatment. Overall, the technique is Art Psychotherapy effective for increasing Self Disclosure in vocational high school students.